Development of a 3D-Printable, Porous, and Chemically Active Material Filled with Silica Particles and its Application to the Fabrication of a Microextraction Device - Szynkiewicz, Dagmara; Ulenberg, Szymon; Georgiev, Paweł; Hejna, Aleksander; Mikolaszek, Barbara; Bączek, Tomasz; Baron, Gino V; Denayer, Joeri F M; Desmet, Gert; Belka, Mariusz (Analytical chemistry (Washington), 2023)
We report on the first successful attempt to produce a silica/polymer composite with retained C18 silica sorptive properties that can be reliably printed using three-dimensional (3D) FDM printing. A 3D printer provides an exceptional tool for producing complex objects in an easy and inexpensive manner and satisfying the current custom demand of research. Fused deposition modeling (FDM) is the most popular 3D-printing technique based on the extrusion of a thermoplastic material. The lack of appropriate materials limits the development of advanced applications involving directly 3D-printed devices with intrinsic chemical activity. Progress in sample preparation, especially for complex sample matrices and when mass spectrometry is favorable, remains a vital research field. Silica particles, for example, which are commonly used for extraction, cannot be directly extruded and are not readily workable in a powder form. The availability of composite materials containing a thermoplastic polymer matrix and dispersed silica particles would accelerate research in this area. This paper describes how to prepare a polypropylene (PP)/acrylonitrile-butadiene-styrene (ABS)/C18-functionalized silica composite that can be processed by FDM 3D printing. We present a method for producing the filament as well as a procedure to remove ABS by acetone rinsing (to activate the material). The result is an activated 3D-printed object with a porous structure that allows access to silica particles while maintaining macroscopic size and shape. The 3D-printed device is intended for use in a solid-phase microextraction (SPME) procedure. The proposed composite's effectiveness is demonstrated for the microextraction of glimepiride, imipramine, and carbamazepine. The complex honeycomb geometry of the sorbent has shown to be superior to the simple tubular sorbent, which proves the benefits of 3D printing. The 3D-printed sorbent's shape and microextraction parameters were fine-tuned to provide satisfactory recoveries (33-47%) and high precision (2-6%), especially for carbamazepine microextraction.